THE ROLE OF NATIONAL INDEPENDENCE IN THE RESTORE OF SPIRITUALITY - Uzoqova Gulzoda Bahrom qizi (Web of Journals Publishing, 2024)
This chapter analyzes the process of national identity recognition and spiritual restoration following Uzbekistan’s achievement of independence. Independence has created new opportunities to restore historical memory, preserve, and develop national values. The revival of historical figures and cultural heritage of the Uzbek people has strengthened national pride and self-awareness.
Keywords: National independence, spirituality, historical memory, national pride, self-identity, Uzbekistan, historical figures.